Learning C# programming with Unity 3D - Okita, Alex (A K Peters/CRC Press, 2020)
Learning C# Programming with Unity 3D, Second Edition is for the novice game programmer without any prior programming experience. Readers will learn how C# is used to make a game in Unity 3D. Many example projects provide working code to learn from and experiment with. As C# evolves, Unity 3D evolves along with it. Many new features and aspects of C# are included and explained. Common programming tasks are taught by way of making working game mechanics. The reader will understand how to read and apply C# in Unity 3D and apply that knowledge to other development environments that use C#. New to this edition: includes latest C# language features and useful tools included with the .NET library like LINQ, Local Functions Tuples, and more! Key Features Provides a starting point for the first-time programmer C# Code examples are simple short and clear Learn the very basics on up to interesting tricks which C# offers. - Resumé vydavatel
Keywords: počítačové hry; programování; C# (programovací jazyk); trojrozměrné zobrazování; computer games; programming; C# (programming language); three-dimensional imaging; elektronické knihy; příručky; electronic books; handbooks and manuals